Potensi Tanaman Iris Air (Iris pseudacorus) sebagai Agen Bioremediasi pada Limbah Air Rumah Tangga di Laut Dendang - Oktaviani, Jelita; Nurjannah, Sekar; Melani, Yohana; Sulastri Simanjuntak, Yolanda; Febriyossa, Adelia; Nilan Sari Rangkuti, Marlinda (Jurnal Biogenerasi, 2024)
This research evaluates the potential of Iris pseudacorus as a bioremediation agent toreduce household wastewater pollution. Using an experimental approach, wastewater samples with different concentrations (1200 ml, 1000 ml, 700 ml, and 500 ml) were tested with Iris water for 10 days. Parameters such as pH, TDS, temperature, turbidity, and odor were observed periodically. Results showed that Iris pseudacorus effectively increased pH, reduced odor, and removed turbidity, and maintained TDS stability, indicating the ability of this plant to absorb pollutants and improve wastewater quality. This study concludes that Iris pseudacorus has strong potential as a bioremediation agent to improve water quality and support environmental sustainability.